Water consumption monitoring system for public bathing facilities - Felgueiras, Carlos (2018)
The European Commission has been developing efforts resulting in directives and programs to stimulate water saving. The lack of information about water usage in public bathing facilities is an obstacle to achieve an adequate management. This work proposes a monitoring system able to observe individual water consumption in public bathing facilities. Gathered information will be used to characterize user behaviour, or even to drive changes in their attitudes.